Hubungan Penerapan Surgical Safety Checklist Dengan Infeksi Luka Operasi (ILO) Di Ruang Operasi Rumah Sakit Murni Teguh Medan - Mendrofa, Ariman; Banjarnahor, Seriga (Universitas Murni Teguh, 2024)
The Surgical Safety Checklist (SSC) is basically a description of patient safety behavior that must be implemented when carrying out activities in the operating room. Use of the Surgical Safety Checklist (SSC) in patient care in accordance with nursing process standards including the quality of work of the operating room nursing team. The use of SSC provides many benefits, especially in reducing incidents that endanger patient safety. Patient safety is a system used to reduce the death rate of surgical patients, which is divided into three stages, namely Sign in, Time out, and Sign out. The aim of the research is to determine whether there is a relationship between the application of the surgical safety checklist and surgical wound infections (ILO) in Murni Teguh Medan. The research method used is quantitative with a cross sectional research design. This research sample used a purposive sampling technique with a total of 87 respondents. The results of this research showed that 84 people (96.6%) applied the surgical safety checklist in the applied category, and 3 (3.4%) did not apply it. The results of the Spearman correlation test obtained a value of p = 0.00 < 0.05. It was concluded that there was a relationship between the application of the surgical safety checklist and surgical wound infections in Murni Teguh Hospital in Medan. Future researchers can conduct research with different variables such as the application of a surgical safety checklist to increase patient safety. Abstrak Surgical Safety Checklist (SSC) pada dasarnya adalah penggambaran perilaku keselamatan pasien yang harus diterapkan dalam pelaksanaan kegiatan di kamar operasi. Penggunaaan Surgical Safety Checklist (SSC) dalam perawatan pasien yang sesuai dengan standar proses keperawatan termasuk kualitas kerja tim perawat kamar operasi. Penggunaan SSC memberikan banyak manfaat terutama dalam mengurangi insiden yang membahayakan keselamatan pasien. Keselamatan pasien adalah suatu sistem yang digunakan untuk mengurangi angka kematian pasien pembedahan, yang dibagi ke dalam tiga tahap yaitu Sign in, Time out), dan Sign out. Tujuan penelitian yaitu untuk mengetahui ada hubungan penerapan surgical safety checklist dengan infeksi luka opersi (ILO) di Murni Teguh Medan. Metode penelitian yang digunakan adalah kuantitatif dengan desain penelitian cross sectional. Sampel penelitian ini menggunakan teknik purposive sampling dengan berjumlah 87 responden. Hasil penelitian ini terdapat penerapan surgical safety checklist dalam kategori diterapkan sebanyak 84 orang (96.6%), dan tidak diterapkan sebanyak 3 (3,4%). Hasil uji korelasi spearman diperoleh nilai p=0,00 < 0.05. Disimpulkan bahwa terdapat hubungan penerapan surgical safety checklist dengan infeksi luka operasi di Rumah Sakit murni teguh Medan. Pada peneliti selanjutnya dapat melakukan penelitian dengan variabel yang berbeda seperti penerapan surgical safety checklist dengan peningkatan keselamatan pasien.